Analisis E-Service Quality Terhadap Loyalitas Nasabah dengan Kepuasan Sebagai Variabel Intervening - Megasari Gusandra Saragih; Desi Astuti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The study was conducted to analyze the effect of e-service quality on customer loyalty mediated by satisfaction. The sample in this study were 135 customers of PT Bank Rakyat Indonesia (BRI) Medan Branch Office Gatot Subroto Street, Medan. This research is a quantitative research with primary data sources, namely by distributing questionnaires to respondents with a Likert scale of 1-5. The analytical method used is a tiered structure with Structural Equation Modeling (SEM) using the AMOS-20 (Analysis of Moment Structure) device. The results showed that e-service quality had a significant effect on customer satisfaction and loyalty at BRI Medan Branch Office. Satisfaction has a significant effect on customer loyalty at BRI Medan Branch Office. Satisfaction partially mediates the effect of e-service quality on customer loyalty at BRI Medan Branch Office